Chemical synthesis and characterization of silver-protected vasoactive intestinal peptide nanoparticles. (December 2009) - Fernandez-Montesinos, Rafael; Castillo, Paula M; Klippstein, Rebecca; Gonzalez-Rey, Elena; Mejias, Jose A; Zaderenko, Ana P; Pozo, David
We characterized a method to conjugate functional silver nanoparticles with vasoactive intestinal peptide (VIP), which could be used as a working model for further tailor-made applications based on VIP surface functionality. Despite sustained interest in the therapeutic applications of VIP, and the fact that its drugability could be largely improved by the attachament to functionalized metal nanoparticles, no methods have been described so far to obtain them.Materials & methods: VIP was conjugated to tiopronin-capped silver nanoparticles of a narrow size distribution, by means of proper linkers, to obtain VIP functionalized silver nanoparticles with two different VIP orientations (Ag––tiopronin––PEG––succinic––[His]VIP and Ag––tiopronin––PEG––VIP[His]). VIP intermediate nanoparticles were characterized by transmission-electron microscopy and Fourier transform infrared spectroscopy. VIP functionalized silver nanoparticles cytotoxicity was determined by lactate dehydrogenase release from mixed glial cultures prepared from cerebral cortices of 1––3 days-old C57/Bl mice. Cells were used for lipopolysaccharide stimulation at day 18––22 of culture.Results: Two different types of VIP-functionalized silver nanoparticles were obtained; both expose the C-terminal part of the neuropeptide, but in the first type VIP is attached to silver nanoparticle through its free amine terminus (Ag––tiopronin––PEG––succinic––[His]VIP), while in the second type, VIP N-terminus remains free (Ag––tiopronin––PEG––VIP[His]). VIP-functionalized silver nanoparticles did not compromise cellular viability and inhibited microglia-induced stimulation under inflammatory conditions.Conclusion: The chemical synthesis procedure developed to obtain VIP-functionalized silver nanoparticles rendered functional products, in terms of biological activity. The two alternative orientations designed, reduced the constraints for chemical synthesis that depends on the nanosurface to be functionalized. Our study provides, for the first time, a proof of principle to enhance the therapeutic potential of VIP with the valuable properties of metal nanoparticles for imaging, targeting and drug delivery.